Intrinsic and extrinsic motivation, mathematics problem-solving performance in graded and non-graded work - Aberin, Maria Alva Q. (2006)
This study aimed to develop a motivational development strategy that will enhance the intrinsic and extrinsic motivation towards the learning of Mathematics of freshmen college students. Two classes enrolled in a 6-unit course in calculus participated in the study where one class was exposed to the traditional motivational development strategy while the other class to the Enhanced Intrinsic-Extrinsic (EIE) Motivational Development Strategy. It was revealed that students who are high in mathematical ability and intrinsic motivation performed better in non-graded problem solving work than those with low mathematical ability. Students with high level of intrinsic motivation provided solutions that are less time-consuming, more complete, and concise than those with low level of intrinsic motivation.